2011
DOI: 10.1002/da.20877
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioral group therapy versus group psychotherapy for social anxiety disorder among college students: a randomized controlled trial

Abstract: Treatment of SAD appears to be moving toward individual CBT, partly because of high attrition rates and underutilization of group dynamics in group CBT. However, group therapy has unique therapeutic ingredients, and it may be too early to give up on group treatment altogether. Discussion of these findings included future directions with this treatment modality, especially whether these two types of group treatment could be combined and whether such combination might serve to decrease attrition, enhance efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 41 publications
1
19
2
Order By: Relevance
“…One study of group versus individual cognitive behavioral therapy for social anxiety disorder found equivalent effects in both groups and remarked that social anxiety disorder treatment has been moving towards individual rather than group because of high attrition rates and under-utilization of group dynamics (Bjornsson et al, 2011). Another study looking at group versus individual therapy for workplace depression found no difference between groups at a one-year follow-up (Sandahl et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One study of group versus individual cognitive behavioral therapy for social anxiety disorder found equivalent effects in both groups and remarked that social anxiety disorder treatment has been moving towards individual rather than group because of high attrition rates and under-utilization of group dynamics (Bjornsson et al, 2011). Another study looking at group versus individual therapy for workplace depression found no difference between groups at a one-year follow-up (Sandahl et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure therapy allows clients to engage in experiments that aim to disprove unrealistic beliefs caused by excessive anxiety (Arch & Craske, 2008). Numerous studies have demonstrated the efficacy of CBT approaches (individual and group) for the treatment of SAD in children and adults (for reviews, see Bjornsson et al, 2011;Heimberg, 2002;Wersebe, Sijbrand, & Cuijpen, 2013).…”
Section: Cognitive Behavioral Therapymentioning
confidence: 99%
“…Overall, the various combinations of treatment appear to be effective in reducing fear of negative evaluation. Heimberg's CBGT, which combines cognitive restructuring and exposure, led to significant improvement in fear of negative evaluation across several studies (Bjornsson et al, 2011;Cox, Ross, Swinson, & Direnfeld, 1998;Gelernter et al, 1991;Gruber et al, 2001;Heimberg et al, 1985;Heimberg et al, 1990;Heimberg et al, 1998;Hope, Heimberg, & Bruch, 1995;Hope, Herbert, & White, 1995). These changes were maintained at follow-up with the exception of the five-year follow-up, in which improvement in fear of negative evaluation had diminished somewhat .…”
Section: Fear Of Negative Evaluationmentioning
confidence: 65%
“…Although changes in fear of negative evaluation for CBGT were sometimes not as strong as exposurealone (Hope, Heimberg & Bruch, 1995) or phenelzine at post-test, these differences dissipated during the follow-up periods . Furthermore, CBGT and a non-specific group therapy treatment did not differ in reduction of BFNE scores at post-treatment in college students with SAD (Bjornsson et al, 2011). However, the ES treatment used as an attentional control in Heimberg's work resulted in similar or smaller changes in fear of negative evaluation compared with CBGT.…”
Section: Fear Of Negative Evaluationmentioning
confidence: 88%